Potential Lignocellulolytic Microfungi from Pineapple Plantation for Composting Inoculum Additive - Bambang Irawan; Inten Wahyuningtias; Niken Ayuningtyas; Ola Apriyani Isky; Salman Farisi; Sumardi Sumardi; Afandi Afandi; Sutopo Hadi (International Journal of Microbiology)
Pineapple plantations leave a lot of plant biomass after the planting season ends. The abundant residue of pineapple plants causes problems due to the high content of lignocellulose, which is difficult to decompose naturally. This study aimed to isolate and characterize lignocellulolytic microfungi isolates from pineapple plantations. The information of this study was used as data to prepare an inoculum for the induction of pineapple litter composting that was resistant to stress to pineapple plantation habitat. The results showed that there were 11 dominant lignocellulolytic microfungi isolates found from pineapple litter and plantation soil. Using selective media, the selection showed five cellulolytic (Bioggp 3, 6, 9, 11, and 12); five xylanolytic (Bioggp 3, 6, 8, 9, and 12); and two ligninolytic microfungi isolates (Bioggp 2 and 5). Bioggp 3, 6, 9, and 12 are cellulolytic and xylanolytic with Bioggp 3 showing the highest cellulolytic index (4.0) and xylanolytic index (4.20). Testing of ligninolytic microfungi showed that the Bioggp 5 isolate had a stronger lignin indicator (color intensity = 4.0 and zone ratio of 1.47) than the Bioggp 2 isolate. Bioggp 9 had the highest cellulolytic isolate spore productivity at 4.5 × 108 spores/mL with 93.3% spore viability, and Bioggp 3 had the highest xylanolytic isolate spore productivity at 2.5 × 109 spores/mL with 89.3% spore viability. Bioggp 2 had the highest ligninolytic isolate spore productivity at 1.8 × 109 spores/mL, but Bioggp 5 showed the highest spore viability at 98.0%.